Middle Palaeolithic technical behaviour: Material import- export and Levallois production at the SU 13 of Oscurusciuto rock shelter, Southern Italy. (2016) - Marciani, Giulia; Spagnolo, Vincenzo; Aureli, Daniele; Ranaldo, Filomena; Boscato, Paolo; Ronchitelli, Annamaria
No abstract available